The pH Signaling Transcription Factor PAC-3 Regulates Metabolic and Developmental Processes in Pathogenic Fungi - Martins, Maíra Pompeu; Martinez-Rossi, Nilce M.; Sanches, Pablo R.; Gomes, Eriston Vieira; Bertolini, Maria Célia; Pedersoli, Wellington R.; Silva, Roberto Nascimento; Rossi, Antonio (Frontiers in Microbiology, 2019)
The zinc finger transcription factor PAC-3/RIM101/PacC has a defined role in the secretion of enzymes and proteins in response to ambient pH and also contributes to the virulence of species. Herein we evaluated the role of PAC-3 in the regulation of Neurospora crassa genes, in a model that examined the plant-fungi interactions. N. crassa is a model fungal species capable of exhibiting dynamic responses to its environment by employing endophytic or phytopathogenic behavior according to a given circumstance. Since plant growth and productivity are highly affected by pH and phosphorus (P) acquisition, we sought to verify the impact that induction of a ∆pac-3 mutation would have under limited and sufficient Pi availability, while ensuring that the targeted physiological adjustments mimicked ambient pH and nutritional conditions required for efficient fungal growth and development. Our results suggest direct regulatory functions for PAC-3 in cell wall biosynthesis, homeostasis, oxidation-reduction processes, hydrolase activity, transmembrane transport, and modulation of genes associated with fungal virulence, thereby advancing the current understanding regarding colonization and adaptation processes in response to challenging environments. We have also provided comprehensive evidence that suggests a role for PAC-3 as a global regulator in plant pathogenic fungi, thus presenting results that have the potential to be applied to various types of microbes, with diverse survival mechanisms.